Enhancing Surface Properties Through the Applications of Silica Superhydrophobic Coating - Widati, Alfa Akustia; Salsabilah, Andina Fitriyah; Aisyah, Aisyah; Rahmawati, Zeni; Wan Abdullah, Wan Nazwanie (Indonesian Journal of Chemistry, 2025)
Superhydrophobic silica coatings have gained enormous attention due to their significant contribution to self-cleaning, anti-fouling, anti-icing, anti-corrosion, and moisture-resistance. This mini-review provides an overview of silica surface modification, including functionalization, roughness control, and deposition methods. Functionalization aims to reach hydrophobic properties by the application of low surface energy compounds. Surface roughness control at the micro- and nano-scale across different scales also results in various surface topographies. The type of deposition technique also influences the coating surface properties, including roughness texture, adhesion, and coating thickness. This paper also explains the challenges and gaps of research rarely reported by previous studies, such as the stability of coating in harsh environments, scalability, cost-effectiveness, and sustainability. Furthermore, this article also addresses promising future innovations in developing long-lasting coatings, multifunctional properties, and economic points of view.